The Mediating Impact of Employee Company Identification on Ethical Leadership and Employee Engagement - Bou Samra, Waad (2021)
This study examines the relationship between ethical leadership and employee engagement in the presence of employee company identification, and whether perceived organizational politics have a moderating effect on the relationship between ethical leadership and employee company identification. To our knowledge, researches that studied these constructs and their relationships are scarce, and we expect to fill this gap in the literature. Drawing upon the social exchange, ethics, perceived organizational politics theories a conceptual model was developed and empirically tested. The study was conducted in Lebanon where questionnaires were collected from employees working in different industries. Data were analyzed using SPSS and Smart PLS. The results of our study provided support to the direct relationships and indicated that employee company identification fully mediated the relationship between ethical leadership and employee engagement. In addition, there was no evidence in this study that perceived organizational politics have any moderating impact on this relationship. The findings of this study provide theoretical and practical contributions.